2019
DOI: 10.15171/japid.2019.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonsurgical periodontal therapy on the level of salivary antioxidants in patients with generalized moderate-to-severe chronic periodontitis

Abstract: Background. In the course of periodontal diseases, polymorphonuclear leukocytes (PMNs) produce oxidative agents and free radicals, thus triggering oxidant-antioxidant disequilibrium in the saliva. Due to the reduction of antioxidant protective effect, oxidative stress is induced, destroying periodontal tissues. This study aimed to investigate the consequences of the non-surgical phase of periodontal therapy on the level ofsalivary antioxidantsin patients with generalized moderate-to-severe chronic periodontiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(70 reference statements)
3
0
0
Order By: Relevance
“…The improvement in periodontal status through non-surgical periodontal therapy increased salivary uric acid levels. Our result reflects those of Sayar et al who observed a rise in uric acid levels with improvement in the periodontal status [ 31 ]. Bacterial invasion can cause a loss of balance between ROS and antioxidant defense, which contributes to the pathogenesis of periodontal disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The improvement in periodontal status through non-surgical periodontal therapy increased salivary uric acid levels. Our result reflects those of Sayar et al who observed a rise in uric acid levels with improvement in the periodontal status [ 31 ]. Bacterial invasion can cause a loss of balance between ROS and antioxidant defense, which contributes to the pathogenesis of periodontal disease.…”
Section: Discussionsupporting
confidence: 92%
“…The elimination of oxidative stress results in variations in the levels of uric acid, suggesting potential biomarkers for oral health [ 30 ]. Similar results were obtained by Sayar et al and Baz et al in gingivitis patients following non-surgical therapy [ 31 , 32 ]. An increase in salivary uric acid levels in periodontitis patients was attributed to a decrease in the abundance of free radicals following periodontal treatment [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that salivary uric acid increased in periodontopathic patients after the non-surgical treatment. This result was also gained by Sayar et al [ 129 ] and Baz et al [ 130 ]. The non-surgical treatment allows for a decrease in the concentration of bacterial and oxidative stress products.…”
Section: Studies Of Possible Biomarker For Periodontitissupporting
confidence: 76%